Influence of the façades convective heat transfer coefficients on the thermal energy demand for an urban street canyon building. (September 2017) - Colucci, C.; Mauri, L.; Grignaffini, S.; Romagna, M.; Cedola, L.; Kanna, R.
Abstract: In an urban micro-climate environment, the convective heat transfer coefficient (CHTC) on the façades influences simulated building's energy demand and exterior wall surfaces temperatures. In this paper, it is analyzed how the CHTC values on the façades of a building located in an urban canyon influence the façades temperatures and how important is the choice of an accurate CHTC correlation on the space cooling and heating energy demand. CHTC correlations found in literature are based on some specific micro-climate parameters such as local wind speed, district construction density, temperature differences between façades and canyon air and wind direction. An accurate choice of the right correlation for the simulated urban environment is important to better represent the exterior walls heat removal due to outside wind climate. The effects of the use of different CHTC correlations have been evaluated by means of TRNSYS 17.0 simulation program. The study is performed for a building sited an urban street canyon with the aspect ratio H/W=1 and located in a Mediterranean climate, in Rome. The comparison performed between the results of the numerical simulations shows that some correlations lead to an underestimation of the space heating demand around 9.7% and to an overestimation of the space cooling demand around 17.5%.